2021
DOI: 10.18502/kss.v5i5.8856
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Value of Restaurant Food Waste in Bogor

Abstract: Food loss occurs in urban area restaurants, including in Bogor. The consumption activity in restaurants sometimes produces food waste, including of rice, vegetables or side dishes. The research objectives were (1) To identify the restaurant food-wasting process in Bogor, and (2) To estimate the amount and economic value of restaurant food waste in Bogor. The Indonesian National Standard (SNI) 19-3964-1994 about Sampling and Measurement Method and Composition of Urban Waste was used for sampling. Food waste in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The pricing is determined on a per-area basis of the farm rather than by volume of use, which is how water is priced for household and industrial use. However, a study in two villages in Bogor and Kudus districts reported that payment has not been strictly enforced and most farmers (66%) do not pay due to their belief that water delivery and services by the P3A are unsatisfactory (Syaukat et al, 2014). Low payment and dissatisfaction is despite the relatively small fees-ranging between IDR 25,000-350,000 per hectare per planting season with a median of IDR 100,000-120,000 (Interview 6; Rahman et al, 2019;Syaukat et al, 2014).…”
Section: Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The pricing is determined on a per-area basis of the farm rather than by volume of use, which is how water is priced for household and industrial use. However, a study in two villages in Bogor and Kudus districts reported that payment has not been strictly enforced and most farmers (66%) do not pay due to their belief that water delivery and services by the P3A are unsatisfactory (Syaukat et al, 2014). Low payment and dissatisfaction is despite the relatively small fees-ranging between IDR 25,000-350,000 per hectare per planting season with a median of IDR 100,000-120,000 (Interview 6; Rahman et al, 2019;Syaukat et al, 2014).…”
Section: Availabilitymentioning
confidence: 99%
“…However, a study in two villages in Bogor and Kudus districts reported that payment has not been strictly enforced and most farmers (66%) do not pay due to their belief that water delivery and services by the P3A are unsatisfactory (Syaukat et al, 2014). Low payment and dissatisfaction is despite the relatively small fees-ranging between IDR 25,000-350,000 per hectare per planting season with a median of IDR 100,000-120,000 (Interview 6; Rahman et al, 2019;Syaukat et al, 2014). Several studies on farmers' willingness to pay suggest that farmers are willing not only to pay, but to pay a higher rate if service quality improves (Rahman et al, 2019;Syaukat et al, 2014).…”
Section: Availabilitymentioning
confidence: 99%
See 1 more Smart Citation